A trapped field of 17.6T in melt-processed, bulk Gd-Ba-Cu-O reinforced with shrink-fit steel - Durrell, J H; Dennis, A R; Jaroszynski, J; Ainslie, M D; Palmer, K G B; Shi, Y-H; Campbell, A M; Hull, J; Strasik, M; Hellstrom, E E; Cardwell, D A (Superconductor science & technology, 2014)
The ability of large-grain (RE)Ba sub(2)Cu sub(3)O sub(7-) delta ((RE)BCO; RE = rare earth) bulk superconductors to trap magnetic fields is determined by their critical current. With high trapped fields, however, bulk samples are subject to a relatively large Lorentz force, and their performance is limited primarily by their tensile strength. Consequently, sample reinforcement is the key to performance improvement in these technologically important materials. In this work, we report a trapped field of 17.6 T, the largest reported to date, in a stack of two silver-doped GdBCO superconducting bulk samples, each 25 mm in diameter, fabricated by top-seeded melt growth and reinforced with shrink-fit stainless steel. This sample preparation technique has the advantage of being relatively straightforward and inexpensive to implement, and offers the prospect of easy access to portable, high magnetic fields without any requirement for a sustaining current source.